2010
DOI: 10.1111/j.1365-4632.2010.04471.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of dermatomyofibroma (plaque‐like dermal fibromatosis)

Abstract: Dermatologists and pediatricians should be aware of this benign entity in order to avoid unnecessary treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In the 34 reported pediatric dermatomyofibromas, including our cases (Tables 1 and 2), the youngest patient was 11 months old at diagnosis, 14 although in one case the mother stated that the lesion was present at birth 11 and in another one, since the child was 2 months old 14 . Therefore, the existence of congenital dermatomyofibroma cannot be excluded.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the 34 reported pediatric dermatomyofibromas, including our cases (Tables 1 and 2), the youngest patient was 11 months old at diagnosis, 14 although in one case the mother stated that the lesion was present at birth 11 and in another one, since the child was 2 months old 14 . Therefore, the existence of congenital dermatomyofibroma cannot be excluded.…”
Section: Discussionmentioning
confidence: 74%
“…Dermatomyofibroma has been seldom described in pediatric patients. In our review of the international literature, we found only 22 cases, all of which were published as case reports or included in series with adult patients 1–14 . In one third of the reported cases, only limited information was available 2,13 …”
mentioning
confidence: 99%
“…Surgical excision is the treatment of choice with a low relapse rate even after incomplete excision (Gill, Arlette, Shiau, & Abi Daoud, ; Hügel, ; Mentzel & Kutzner, ). Most common single lesions are observed by multiple lesions have been described in rare cases (Campagnolo et al, ; Cano Martínez, Fernández‐Antón Martínez, Barchino Ortiz, Lecona Echevarría, & Campos Domínguez, ; Gomez‐Moyano, Vera‐Casaño, Martinez‐Garcia, Sanz‐Trelles, & Crespo‐Erchiga, ; Guillen & Requena, ; Hügel, ; Ma, Wieland, & Tollefson, ; Macedo, Mann, Zimmerman, Alves Mde, & Daxbacher, ; Mentzel & Kutzner, ; Romaní, Leal, Sáez, & Luelmo, ; Tardío et al, ; Viglizzo, Occella, Calonje, Nozza, & Rongioletti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dermatomyofibroma is an uncommon benign cutaneous tumor with fibroblastic and myofibroblastic differentiation . It is mainly found in young women and is usually located on the shoulder and adjacent regions, with only a few cases reported in males .…”
Section: Discussionmentioning
confidence: 99%